Translation techniques and error analysis based on the example of the Old Croatian translation of Zrcalo člověčaskago spasenja (1445) from Old Czech. - Kramarić, Martina (Zeitschrift für Slawistik, 2016)
During their residence in Prague (Emaus) in the 14 and 15 centuries, Croatian Glagolitic monks translated a series of medieval religious works from Old Czech into Old Croatian. The best preserved and largest of all these translations is the Glagolitic script Zrcalo člověčaskago spasenja, which was transcribed by hand after its translation in Emaus by Deacon Luka in 1445 in Vrbnica on the island of Krk. This text is part of the Vatican Miscellany, better known as the Miscellany of Deacon Luka. This paper will discuss the translation techniques used, paying special attention to the translator and his level of knowledge of the Old Czech language. Since the earliest studies on the text, it has been said to be incomprehensible in many places due to the Old Czech template and the great deal of errors made during the translation and transcription process. Based on certain observed errors, Stjepan Ivšić concluded that the translator was Croatian. Since a copy of the Old Czech template has been preserved - a complete variant in the Krumlov Miscellany - this paper will attempt to identify and classify as-of-yet unobserved mistakes in the Old Croatian translation, using applied linguistics methods. The Latin original, the prose poem Speculum humanae salvationis will serve as the corrective. The analysis will incorporate both error analysis and translation theory, and the translation type and techniques will be discussed. We believe that this type of analysis will contribute to the better understanding and popularization of this insufficiently studied Old Croatian manuscript.